Applications and implications of neurochemical biomarkers in environmental toxicology. (12th December 2014) - Basu, Niladri
Abstract Thousands of environmental contaminants have neurotoxic properties, but their ecological risk is poorly characterized. Contaminant‐associated disruptions to animal behavior and reproduction, both of which are regulated by the nervous system, provide decision makers with compelling evidence of harm, but such apical endpoints are of limited predictive or harm‐preventative value. Neurochemical biomarkers, which may be used to indicate subtle changes at the subcellular level, may help overcome these limitations. Neurochemical biomarkers have been used for decades in the human health sciences and are now gaining increased attention in the environmental realm. In the present review, the applications and implications of neurochemical biomarkers to the field of ecotoxicology are discussed. The review provides a brief introduction to neurochemistry, covers neurochemical‐based adverse outcome pathways, discusses pertinent strengths and limitations of neurochemical biomarkers, and provides selected examples across invertebrate and vertebrate taxa (worms, bivalves, fish, terrestrial and marine mammals, and birds) to document contaminant‐associated neurochemical disruption. With continued research and development, neurochemical biomarkers may increase understanding of the mechanisms that underlie injury to ecological organisms, complement other measures of neurological health, and be integrated into risk assessment practices. Environ Toxicol Chem 2015;34:22–29. © 2014 SETAC